2012
DOI: 10.1056/nejmoa1110186
|View full text |Cite
|
Sign up to set email alerts
|

Truncations of Titin Causing Dilated Cardiomyopathy

Abstract: BACKGROUND Dilated cardiomyopathy and hypertrophic cardiomyopathy arise from mutations in many genes. TTN, the gene encoding the sarcomere protein titin, has been insufficiently analyzed for cardiomyopathy mutations because of its enormous size. METHODS We analyzed TTN in 312 subjects with dilated cardiomyopathy, 231 subjects with hyper-trophic cardiomyopathy, and 249 controls by using next-generation or dideoxy sequencing. We evaluated deleterious variants for cosegregation in families and assessed clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
1,086
11
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 1,220 publications
(1,219 citation statements)
references
References 40 publications
50
1,086
11
14
Order By: Relevance
“…The TTN A-band was enriched for truncating variants in DCM probands as compared with controls (odds ratio = 14.6; 99% confidence interval: 4.32-58.5; P < 2 × 10 −10 ). The frequency in controls as well as the clustering of variants in the A-band in probands is consistent with results reported by Herman et al 23 In addition, our data showed a reduced frequency of variants in the I-band in probands as compared with controls (odds ratio = 0.13; 99% confidence interval: 0.04-0.43; P < 2 × 10 −6 ). No difference in frequency was detected in the Z-and M-bands (Figure 3).…”
Section: Distribution Of Ttn-truncating Variants In Individuals Withsupporting
confidence: 93%
See 3 more Smart Citations
“…The TTN A-band was enriched for truncating variants in DCM probands as compared with controls (odds ratio = 14.6; 99% confidence interval: 4.32-58.5; P < 2 × 10 −10 ). The frequency in controls as well as the clustering of variants in the A-band in probands is consistent with results reported by Herman et al 23 In addition, our data showed a reduced frequency of variants in the I-band in probands as compared with controls (odds ratio = 0.13; 99% confidence interval: 0.04-0.43; P < 2 × 10 −6 ). No difference in frequency was detected in the Z-and M-bands (Figure 3).…”
Section: Distribution Of Ttn-truncating Variants In Individuals Withsupporting
confidence: 93%
“…From an analysis of 312 DCM patients and 249 controls, Herman et al 23 reported a clustering of truncating variants in the A-band 23 To validate and expand on this finding, we combined the variants from Herman et al 23 (n = 55) with TTN -truncating variants detected in our study (n = 18). The NHLBI ESP cohorts (~6,500 individuals of European or African-American ancestry) served as a control cohort, representing the general population.…”
Section: Distribution Of Ttn-truncating Variants In Individuals Withmentioning
confidence: 54%
See 2 more Smart Citations
“…Prominent examples include MYBPC3 , which explains 15–20% of hypertrophic cardiomyopathy (HCM) and TTN , which is responsible for 10–25% of dilated cardiomyopathy (DCM) (Herman et al. 2012; Teekakirikul et al. 2013; Pugh et al.…”
Section: Introductionmentioning
confidence: 99%